Пропозиція Михайла Маркова щодо викладання історії 1803 р. - Маслійчук, В. (Сiверянський лiтопис, 2015)
У публікації йдеться про ставлення до викладання історії відомого діяча просвітництва у Чернігівській губернії, директора училищ Михайла Маркова на початку XIX ст. Михаил Марков (1760 – 1819) – директор народных училищ Черниговской губернии,
региональный историк. Деятель эпохи Просвещения имел свои взгляды на украинское
прошлое. В 1803 г. он предложил написать учебник по местной истории и географии.
Это первое известное нам предложение о написании учебника по украинской истории. Mykhaylo Markov (1760 – 1819) – the director of people schools (Chernihiv gubernia)
(1800 – 1819) and Chernihiv gymnasium (1805 – 1819), regional historian. Mykhaylo Markov’s
Activity was under the attentive opinions of historians (Oleksiy Andriashev, Mykhaylo
Berezhkov, Mykhaylo Tutolmin, Volodymyr Kravchenko, Oleh Zhurba). It should be recognized
assessment of creativity and activity of Mikhail Markov require many refinements. The
studies of new documents allow us to look better on the figure of this historian and educator.